Effect of iron content on the hydrogen production kinetics of electroless-deposited CoNiFeP alloy catalysts from the hydrolysis of sodium borohydride, and a study of its feasibility in a new hydrolysis using magnesium and calcium borohydrides. (7th June 2019) - Kim, Dong Hyeon; Jo, Seunghyun; Kwon, JunHwa; Lee, Seungmin; Eom, KwangSup
Abstract: The effect of Fe content in electroless-deposited CoNi-Fex -P alloy catalysts (x = 5.5–11.8 at.%) from the hydrolysis of NaBH4 is investigated in alkaline sodium borohydride solution. The electroless-deposited CoNiFe5.5 -P and CoNiFe7.6 -P alloy catalysts are composed of flake-like micron particles; however, with an increase in Fe content to 11.8 at.%, the flake-like morphology is changed to a spherical shape and the crystal structure of the electroless-deposited CoNiFeP catalyst is transformed from FCC to BCC. Among all the CoNi-Fex -P alloy catalysts, the CoNi-Fex -P (x = 7.6 at.%) catalyst has the highest hydrogen production rate of 1128 ml min −1  g −1 catalyst in alkaline solution containing 1 wt% NaOH + 10 wt% NaBH4 at 303 K. For the optimized catalyst, the activation energy of the hydrolysis of NaBH4 is calculated to be 54.26 kJ mol −1 . Additionally, in this work, we report a new hydrolysis using Mg(BH4 )2 and Ca(BH4 )2 . As a result, the Mg(BH4 )2 is stored unstably in an alkaline solution, whereas the Ca(BH4 )2 is stored stably. When optimizing the hydrogen production kinetics from the hydrolysis of Ca(BH4 )2, the rate is 784 ml min −1  g −1 catalyst in 10 wt% NaOH + 3 wt% Ca(BH4 )2 solution. Highlights: CoNi-Fex -P catalysts (x = 5.5–11.8 at.%) are prepared by electroless deposition. The morphology and crystal structure of the catalysts are varied with Fe content. The CoNiFe7.6 -P catalyst has the highest hydrogen production rate. The hydrogen production rate is well maintained after cyclic durability test. New hydrolysis reactions using Ca(BH4 )2 and Mg(BH4 )2 are also investigated.